„Tà apórreta” w prawie ateńskim - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article is devoted to tà apórreta — “forbidden words” in Athenian law, a groundless use of which could lead to a defamation charge (díke kakegorías). The apórreta catalogue included terms like androphónos (“mankiller”), metraloías (“mother beater”), patraloías (“father beater”), apobeblekénai ten aspída, i.e. accusation of abandoning one’s shield on a battlefield as well as accusation of undertaking paid work on the agora levelled against an Athenian citizen. After presenting the sources making it possible to partly reconstruct the catalogue of the “forbidden words”, the author analyses the various apórreta. Next, he presents theories explaining the reasons why these terms were proclaimed forbidden and tries to determine when the law in question was adopted
Keywords: athenian law; defamation; slander